Enhanced electrocatalytic performance of interconnected Rh nano-chains towards formic acid oxidation - Sathe, Bhaskar R.; Balan, Beena K.; Pillai, Vijayamohanan K. (Energy & Environmental Science, 2011)
A chain-like assembly of rhodium nanoparticles (5-7 nm mean diameter) has been synthesized from rhodium chloride with the help of polydentate molecules like tartaric and ascorbic acids (1 : 3 in mM scale) as capping agents at room temperature. Subsequent characterization using transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy reveals a unique inter-connected network like features, while their electrochemical behavior using cyclic voltammetry and current-time transient suggests potential applications as electrocatalysts in fuel cells. A significant negative shift in the onset potential as well as higher anodic peak current density for formic acid oxidation on Rh-tartaric acid (Rh-TA) as compared to that of bulk Rh metal confirms their higher electrocatalytic activity. Interestingly, the enhancement factor (R) with respect to that of bulk metallic Rh towards formic acid oxidation ranges up to 2000% for Rh-TA and 1200% for Rh-AA (Rh-ascorbic acid) respectively. The composition of Rh nano-chains has been further analyzed with thermogravimetry and Fourier transform infra-red spectroscopy to demonstrate the importance of controlling the chain topology using polyfunctional organic molecules. These findings open up new possibilities for tailoring nanostructured electrodes with potential benefits since the development of a better electrocatalysts for many fuel cell reactions continues to be an important challenge.